EPEN-36. THE TREATMENT OUTCOME OF PAEDIATRIC SUPRATENTORIAL C11ORF95-RELA FUSED EPENDYMOMA: A COMBINED REPORT FROM E-HIT SERIES AND AUSTRALIAN NEW ZEALAND CHILDREN'S HAEMATOLOGY/ONCOLOGY GROUP. (4th December 2020) - Ng, Chia Huan; Obrecht, Denise; Buntine, Molly; Wells, Olivia; Campbell, Martin A; Bhatia, Kanika; Sullivan, Michael; Williams, Molly; Quang, Dong Anh Khuong; Kinross, Kathryn; White, Christine; Algar, Elizabeth; et al.
Abstract: AIM: Advances in molecular classification of paediatric ependymoma have been pivotal in improving risk stratification and understanding of this disease. C11orf95-RELA fused supratentorial ependymoma (ST-EPN) have been reported to have a poor outcome, with 10-year overall survival (OS) of 49% and progression free survival (PFS) of 19%. A cohort of patients from multiple international institutions with molecularly confirmed C11orf95-RELA fused ST-EPN were reviewed to assess their disease behaviour. METHOD: We reviewed patients with molecularly determined C11orf95-RELA supratentorial ependymoma diagnosed between 1999 – 2019. Demographic information, extent of surgical resection, use of radiotherapy and/or chemotherapy, disease recurrence, treatment at recurrence and clinical outcome data was collected. PFS and OS of all patients were estimated using Kaplan-Meier method. RESULTS: A total of 76 ST-EPN patients with C11orf95-RELA fusion were identified (median age: 7 years3 months, range: 5 months – 18 years7 months). 58 patients (76.3%) had complete surgical resection. 70 patients(92.1%) received radiotherapy. 55 patients(72.3%) received chemotherapy. The 10-year OS of C11orf95-RELA fused ST-EPN was 72.4% and PFS was 63.8%. In contrast, ST-EPN at a single institution with unconfirmed molecular status had an OS of 61.1% and PFS of 34.9%. CONCLUSION: Detailed molecular analysis identified distinct subgroups of patients with ST-EPN. Patients from this cohort with C11orf95-RELA methylation profiles had a significantly higher OS compared to previous reports and those with unconfirmed fusion status, emphasising the critical importance of complete molecular profiling to assist in treatment decision making. Complete molecular analysis in future prospective cohorts is essential for accurate risk stratification and treatment selection.